Graphene-coated hybrid electrocatalysts derived from bimetallic metal–organic frameworks for efficient hydrogen generation. Issue 10 (17th February 2017) - Li, Xiao; Yang, Liu; Su, Tan; Wang, Xinlong; Sun, Chunyi; Su, Zhongmin
Abstract : This is the first example of a Ni and Mo2 C nanocomposite derived from a bimetallicNiMo-MOF that demonstrates excellent electrocatalytic activity and remarkable durability as long as 10 h for HER under acidic and basic conditions. Abstract : In this study, we synthesized a low-cost electrocatalyst, Ni/Mo2 C nanoparticles coated with graphene shells (denoted asNiMo2 C@C ), via a facile carburization process of porous bimetallic metal–organic frameworks (NiMo-MOF ). This is the first example of a Ni and Mo2 C nanocomposite derived from a bimetallic MOF that demonstrates excellent electrocatalytic activity and remarkable durability as long as 10 h under acidic and basic conditions. The overpotentials are 169 mV and 181 mV to reach the current density of 10 mA cm −2, respectively. The favorable performance can be ascribed to the synergistic effect between Mo2 C and Ni as well as the homogeneous distribution, graphene coating and mesoporous structure which is in favor of the charge transfer in the HER. This work may provide some guidelines for fabricating nanostructured hybrids composed of versatile transition metal carbides and graphene with high performance and stability in different media based on designed MOFs.